The Media, the Market and Democracy: The Case of the Philippines - Coronel, Sheila S. (Javnost-The Public, 2001)
The popular mobilisation that led to the downfall of President Estrada in January 2001 was facilitated by the use of new communication technologies, notably text messaging on mobile phones and the establishment of web sites. Public awareness of political developments, fostered by these means and by independent media, eventually forced the main mass media to cover Estrada's impeachment trial, and it was the threat of the collapse of that trial that provoked mass demonstrations. These events illustrate some leading themes in the history of the Philippine's mass media. Newspapers, radio and television have long been privately owned, and have developed into very market-oriented media. Most of the time, they are devoted to tabloid and sensational reporting, and they are mostly closely connected with large and diversified corporations. After a long period of repression by Ferdinand Marcos, his overthrow saw an explosion of genuinely independent media, although issues of ownership and traditions of bribing journalists put limits on what got reported. Estrada attempted to control the media more directly, particularly through systematic bribery, threatening the businesses of media owners with tax audits, and manipulating advertising. For some time, he was successful, but as public awareness of his crimes grew, so audiences demanded better mainstream coverage. The media were forced by their audiences to adopt a much more critical stance, and this opened the way for independent journalism.